Intraoperative biopsy and aspiration of brain lesions under ultrasound guidance-preliminary studies - Mahbar, Zahari; S, Chandrasekharan; Omar, Shukri (1999)
Biopsy of intracranial masses and aspiration of abscesses are important techniques in the management of pathologies affecting the brain.CT scanning is used to detect the presence of a lesion and its approximate location. Intraoperatively however actual localisation of a lesion commonly has been done in two ways.Firstly by rough approximation using the CT scan images and bony landmark as a guide and secondly by CT stereotaxis. The first technique is inexpensive but unfortunately not very accurate. Small lesion may be missed.For abscess aspiration,patient often require repeat CT scanning and often require repeat operations.CT stereotaxis is excellent for localisation but is expensive and cumbersome.The patient need to be rescanned and then transported to the operating theatre from the CT suite without any relative change in position between the patient and the stereotactic equipment.Any change inposition require the patient to be rescanned and the stereotactic equipment adjusted accordingly.